Outsourcing, occupational restructuring, and employee well-being: Is there a silver lining? - Petri Böckerman; Mika Maliranta (The Research Institute of the Finnish Economy (ETLA), 2012)
This paper explores the effects of outsourcing on employee well-being through the use of the Finnish linked employer-employee data. The direct negative effect of outsourcing is attributable to greater job destruction and worker outflow. In terms of perceived well-being, the winners in international outsourcing are those who are capable of performing interactive tasks (i.e., managers, professionals and experts), especially when offshoring involves closer connections to other developed countries.
Keywords: J28; F23; 330; globalization; outsourcing; offshoring; working conditions; job satisfaction; subjective well-being; Outsourcing; Auslandsverlagerung; Arbeitszufriedenheit; Lebensqualität; Finnland